Otalgia sebagai Prediktor Terbentuknya Kolesteatoma pada Otitis Media Supuratif Kronis - Fabiola Cathleen (Cermin Dunia Kedokteran, 2024)
With its locally invasive nature, cholesteatoma has the potential to cause fatal complications. However, many remain undetected until advanced stages. Otalgia is suggested as the indicator of impending intratemporal or intracranial complication and is commonly presented before episodes of characteristic foul-smelling purulent discharge. As an earlier diagnosis of this condition is needed, this study aims to find whether the presence of otalgia has a prognostic value of cholesteatoma formation in adult patients with chronic suppurative otitis media. Literature searching using Pubmed, Cochrane, and ScienceDirect was done from the 12th to 16th of March 2022. Two articles were selected and appraised using the Center of Evidence-Based Medicine Oxford tool for prognostic study. Both studies retrospectively found no statistically significant patient characteristics or clinical presentation findings including otalgia that might guide the distinction between chronic suppurative otitis media on first hospital admission with and without cholesteatoma. Even though all studies have good validity, applicability, and precise prognostic estimates owing to their narrow 95%CI, considerable discrepancies between the two studies exist, therefore clinical interpretation remains questionable. Otalgia does not have a significant prognostic role in cholesteatoma formation in patients with chronic suppurative otitis media.